PSYCOLOGICAL QUESTIONNAIRES AND RESEARCH ON THE INTERNET: A LITERATURE REVIEW - Eiroá Orosa, Francisco José; Fernández Pinto, Irene; Pérez Sales, Pau (Anales de Psicología / Annals of Psychology, 2008)
The growing importance of Internet has changed the world of psychological research, initiating a new research field and opening new sampling perspectives. The present article reviews methodological aspects related to online questionnaires for research purposes. There are some clear advantages: cost reduction, decrease of social desirability effects and access to big population groups. But there are also difficulties derived from potential sampling bias and implementation methods which could be partially compensated. As a whole, the possibilities of questionnaire implementation are as big as the Net, but only through the knowledge of its dynamics, methodological and ethical principles.